TEOLOGI POLITIK YESUS: SUMBANGSIH MATERI BAGI MATA KULIAH PENDIDIKAN AGAMA KRISTEN DI POLITEKNIK AMAMAPARE TIMIKA - Rungkat, Jimmy (Politeknik Amamapare, 2022)
The purpose of this study was to understand the characteristics of Jesus' Political Theology as a contribution to the Christian Education Course at the Politeknik Amamapare Timika. The method used in this research is library research and through hermeneutic-exegesis approach. This research involves the researcher fully to obtain a complete understanding of the intent conveyed by the writer of the scriptures regarding the context that gives meaning by using the processes of text analysis, narrative analysis, and theological meaning. The results show that Jesus' political theology departs from the theme of the Kingdom of God, which is presented on earth as a system of political thought and action that is balanced by every Christian. In its realization, truth and justice have always been the foothold and the Greatness of God is the main goal of various forms of power in the world which is driven by a high dedication to carrying out political duties in helping others who are experiencing difficulties because of feelings, sympathy and empathy on the basis of true love for social problems, characteristics of Jesus' Political Theology as a framework of thought and framework The socio-political role of Christianity in Indonesia is oriented towards the general welfare, synergizing religion and state which rejects state religion and state religion, theocracy in democracy, guarantees human rights, rejects discrimination, and realizes laws that do not impartial and uncompromising.